The price of safety and convenience: Urban shoppers’ willingness to pay for hygienic market stalls and minimal processing of leafy vegetables in Kenya - Mercy Mwambi; Paul Opiyo; Augustine Wafula; Pepijn Schreinemachers; Ralph Roothaert; Julia de Bruyn (PLoS ONE, 2026)
The safety of fresh food is a serious concern across sub-Saharan Africa. Stronger incentives are needed to stimulate market retailers to adopt more hygienic practices and to drive improvements in fresh produce market infrastructure. A price premium for safe produce could incentivize retailers to do this, but it is unknown if shoppers would accept a higher price. The objective of this study was to evaluate the demand for safer vegetables among urban consumers in Africa. The Becker–DeGroot–Marschak (BDM) method was used to conduct a non-hypothetical experimental auction with 417 randomly selected shoppers in five fresh produce markets in Kisumu, Kenya. Shoppers chose between two bundles of mixed African leafy vegetables: (1) whole, unpackaged, and (2) minimally processed vegetables – washed, plucked, and packaged; and two food safety conditions: (3) conventional handling practices in a traditional stall, and (4) hygienic handling in an improved stall based on government guidelines. The results show that shoppers are willing to pay about 24% more for whole vegetables from clean stalls and about 26% more for minimally processed vegetables. Plucked vegetables pose a higher food safety risk than whole vegetables, but wealthier, time-constrained shoppers opt for them for convenience. These findings indicate that urban shoppers in Kenya attach value to the safety of fresh produce. Retailers can command higher prices by enhancing stall hygiene, but external support will be needed to upgrade retail market infrastructure.